An Analysis of Derivational Affixes in Commencement speech By Steve Jobs - Nur, Dedi Rahman (Script Journal: Journal of Linguistic and English Teaching, 2016)
The study expects to an investigation of derivational appends in the content of initiation discourse by Steve Jobs. The essayist utilized the majority of the words that were connected prefix and postfix as the information. The information sources were all content of initiation discourse by Steve Jobs. This study utilizing subjective plan and substance investigation approach. The aftereffect of the study demonstrated that there were 78 all out words in the content of Commencement discourse which joined derivational fastens. The study discovered 69 postfixes and 9 prefixes. The foundations of the words that has been grouped in light of the grammatical feature are 17 (descriptor), 27 (thing), 33 (verb), 1 (adverb).From the finish of this study, the author proposes that to enhance their dominance of vocabulary, the perusers ought to apply the derivational fastens by breaking the word into its components root and attaches in light of the fact that from single word they can get the structure of words and them additionally discover how the words fabricated. By knowing the roots, the perusers can assemble the word without anyone elses input